THE RISK FACTOR OF HYPERTENSION AND SEX TO CORONARY ARTERY DISEASE AT JEMURSARI ISLAMIC HOSPITAL SURABAYA - Hanin Dhany Robby (Universitas Airlangga, 2018)
Coronary Artery Disease (CAD) is one of the non-communicable diseases which need concern nowadays because it leads cause of the death worldwide and estimates attacking more people in year by year. The risk factors of CAD divided into two categories such as modifiable risk and non-modifiable risk presented in this study including hypertension and sex. The study aimed to analyze the risk factor of hypertension and sex to CAD in patients who visited Cardiovascular Polyclinic of Jemursari Islamic Hospital in April 2017. The research was non-reactive study with analytical research design involved 850 respondents as the sample which chosen by systematic random sampling from 2474 people as the population. The data were analyzed with R using test of chi square and test of binary logistic regression. The result showed in chi square test that there was a relationship between hypertension and sex with CAD. In addition, factors of hypertension and sex were significantly related to CAD with the test of binary logistic regression. In conclusion, hypertension and sex were the risk factors of CAD and hypertension and sex were associated with CAD. The study suggested taking anti-hypertensive drugs for the treatment of hypertension in order to reduce the CAD risk, to reduce the consumption of salt and categorized the modifiable risk for men and women as the prevention from sudden coronary death.